Case Report: Intracranial Hypertension Secondary to Guillain-Barre Syndrome - Christina Doxaki; Eleftheria Papadopoulou; Iliana Maniadaki; Nikolaos G. Tsakalis; Konstantinos Palikaras; Pelagia Vorgia (Frontiers Media S.A., 2021)
Guillain-Barre Syndrome (GBS), a common cause of acute flaccid paralysis, is characterized by a rapidly progressive, usually symmetric weakness of the extremities. Headache and intracranial hypertension (ICHT) are very rare complications of GBS. Herein we report our current case of an obese girl with typical signs of GBS associated with autonomic dysfunction, cranial nerve deficits and increased intracranial pressure (ICP). We also perform a systematic study presenting and discussing previous case reports of GBS associated with ICHT, papilledema or hydrocephalus, highlighting the differences of the current case compared to previous studies. Although intracranial hypertension is a rare complication of pediatric GBS, clinicians should promptly detect it. Obesity may be a predisposing factor, given the strong association between idiopathic intracranial hypertension (IIH) and weight gain. Neurological evaluation, fundus examination and low threshold for intracranial imaging should be an integral part of medical practice in case of obesity, headache or visual changes in GBS patients.